Cryptogenic hepatic abscess in an infant and management challenges in a resource limited setting: a case report - Oluwafunmilayo Funke Adeniyi; Nelson Daniel; Olivia Ashefor; Patricia Akintan (SpringerOpen, 2023)
Abstract Background Pyogenic liver abscess is a rare condition in children especially in early infancy. The diagnosis requires a high index of suspicion and treatment has to be aggressive to avoid fatality. There is a rarity of reports of the condition in infancy in the African population. Thus, we report a case of the hepatic abscess with documented hypergammaglobulinemia in a young infant seen at the Lagos University Teaching hospital. Case presentation We describe the case of a 38-day-old female infant who presented with 4 weeks history of fever and 2 weeks history of progressive abdominal distension. At the onset of illness abdominal ultrasound suggested hepatic abscess and abdominal CT scan confirmed multiple loculated collections in 3 segments of the liver. Patient had drainage of the abscess and additional investigations revealed hypergammaglobulinemia (IgM, IgG, and IgE) in the patient. She completed 6 weeks of antibiotics and made significant clinical improvement. Conclusions Pyogenic liver abscess should be considered in the differential diagnosis of an infant with pyrexia with abdominal swelling, even in the absence of well-established risk factors. A high index of suspicion for underlying primary immunodeficiency is important when the condition is diagnosed in early infancy.